Terbinafine‐resistant strain of Trichophyton interdigitale strain isolated from a tinea pedis patient. Issue 4 (15th February 2019) - Hiruma, Junichiro; Kitagawa, Hiroyuki; Noguchi, Hiromitsu; Kano, Rui; Hiruma, Masataro; Kamata, Hiroshi; Harada, Kazutoshi
Abstract: Trichophyton interdigitale is an anthropophilic species that is frequently isolated from tinea unguium and tinea pedis throughout the world. In the present study, antifungal susceptibility testing was performed on T. interdigitale isolates from Japanese patients (isolated in 2017–2018; 24 strains) to assess itraconazole (ITZ) and terbinafine (TRF) susceptibility of these strains. E‐test determinations revealed that the mean ITZ minimum inhibitory concentration (MIC) of the 24 strains was 0.023 mg/L (range, 0.064–1). Clinical Laboratory Standards Institute M38‐A2 determinations revealed that the mean TRF MIC of 23 of the 24 strains was less than 0.03125 mg/L. Among these strains, one (NUBS18016) had a TRF MIC of 2 mg/L, confirming its resistance to TRF. The predicted amino acid sequences of the squalene epoxidase ( SQLE ) gene from the TRF‐resistant strain (NUBS18016) was 100% identical to the SQLE gene sequence of the reference strain T. interdigitale, indicating that no gene mutations were present in NUBS18016. Therefore, the TRF‐resistance mechanism of our TRF‐resistant strain NUBS18016 has not been defined. Dermatologists should be cautious about the prevalence of foot dermatophytosis due to antifungal drug‐resistant strains.